Industry 4.0 and circular economy practices: A new era business strategies for environmental sustainability - Khan, Syed Abdul Rehman; Razzaq, Asif; Yu, Zhang; Miller, Sharon (Business strategy and the environment, 2021)
Amid rising environmental concerns, Industry 4.0 and blockchain technology (BCT) are transforming circular economy (CE) practices and prevailing business models. Recognize the same; this study examines the role of blockchain technology in circular CE practices and their impact on eco‐environmental performance, which influences organizational performance. The study collects data from 404 enterprises located in Chinese and Pakistani territories, involved in cross‐border supply chain operations. Both countries' sample has great relevance due to the China Pakistan Economic Corridor (CPEC), which possesses several positive fallouts in terms of technology spillovers across firms. Using the partial least squares structural equation modeling (PLS‐SEM) modeling framework, this study provides three key findings. First, BCT significantly improves the circular economy practices (circular procurement, circular design, recycling, and remanufacturing). Second, CE practices help improve firms' environmental performance and stimulate their financial performance. Third, higher eco‐environmental performance significantly boosts organizational performance. This study sets out the foundations for participating countries/firms that simultaneously achieve financial and sustainable goals by integrating blockchain technology in circular economy practices.